2020
DOI: 10.1186/s40348-020-00108-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolving pituitary hormone deficits in primarily isolated GHD: a review and experts’ consensus

Abstract: Isolated growth hormone deficiency (GHD) is defined by growth failure in combination with retarded bone age, low serum insulin-like growth factor-1, and insufficient GH peaks in two independent GH stimulation tests. Congenital GHD can present at any age and can be associated with significant malformations of the pituitary-hypothalamic region or the midline of the brain. In rare instances, genetic analysis reveals germline mutations of transcription factors involved in embryogenesis of the pituitary gland and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…In the pediatric population, van Iersel et al [ 26 ] showed in a large retrospective cohort study that rhGH therapy could unmask central hypothyroidism, especially in those initially classified as non-acquired apparent isolated GH-deficient children who had congenital structural pituitary abnormalities. Regardless of the cause of thyroid function alterations during rhGH therapy, most authors agree that there is a need for the regular monitoring of thyroid hormone levels in all GH-deficient children after the initiation of rhGH therapy in order to early identify and correct the possible thyroid function abnormalities that could occur during therapy [ 5 , 13 , 14 , 15 , 23 , 29 ]. Thyroid hormones directly stimulate the transcription of GH, IGF-1 and insulin-like growth factor binding protein-2 (IGFBP-2) and insulin-like growth factor binding protein-4 (IGFBP-4) genes, as well as increasing the mRNA of GH and growth hormone-releasing hormone (GHRH) receptors [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pediatric population, van Iersel et al [ 26 ] showed in a large retrospective cohort study that rhGH therapy could unmask central hypothyroidism, especially in those initially classified as non-acquired apparent isolated GH-deficient children who had congenital structural pituitary abnormalities. Regardless of the cause of thyroid function alterations during rhGH therapy, most authors agree that there is a need for the regular monitoring of thyroid hormone levels in all GH-deficient children after the initiation of rhGH therapy in order to early identify and correct the possible thyroid function abnormalities that could occur during therapy [ 5 , 13 , 14 , 15 , 23 , 29 ]. Thyroid hormones directly stimulate the transcription of GH, IGF-1 and insulin-like growth factor binding protein-2 (IGFBP-2) and insulin-like growth factor binding protein-4 (IGFBP-4) genes, as well as increasing the mRNA of GH and growth hormone-releasing hormone (GHRH) receptors [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, levothyroxine (L-thyroxine) supplementation should be taken into account as a possible way to achieve the optimal growth effect of rhGH therapy [ 27 ]. The clinical significance of thyroid hormone changes during rhGH therapy seemed to be underappreciated despite many authors agreeing that the regular monitoring of thyroid function during rhGH therapy is needed [ 5 , 13 , 14 , 22 , 23 , 24 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…MRI identification of the triad of ectopic posterior pituitary, anterior pituitary hypoplasia and pituitary stalk agenesis is of great value in recognizing patients at risk for evolving pituitary hormone deficiencies. In particular, small size and location of ectopic posterior pituitary are predictive of MPHD development 146,147 .…”
Section: [H3] Hypothalamic-pituitary Mri Anatomy and Pituitary Functi...mentioning
confidence: 99%
“…They also concluded that regular monitoring of thyroid hormone levels during rhGH therapy is not warranted in such children [34]. On the other hand, a recently published expert opinion is that "there are no absolute criteria enabling exclusion of children without any risk of progress to combined pituitary hormone deficiency" [64], and lifelong monitoring of the pituitary gland function is recommended, especially in patients with organic GHD [64].…”
Section: Therapeutic Implications Of the Rhgh Influence On Thyroid Functionmentioning
confidence: 99%